Rapid assessment of quantitative T1, T2 and T2* in lower extremity muscles in response to maximal treadmill exercise. (28th June 2015) - Varghese, Juliet; Scandling, Debbie; Joshi, Rohit; Aneja, Ashish; Craft, Jason; Raman, Subha V.; Rajagopalan, Sanjay; Simonetti, Orlando P.; Mihai, Georgeta
<x xml:space="preserve">Abstract</x> MRI provides a non‐invasive diagnostic platform to quantify the physical and physiological attributes of skeletal muscle at rest and in response to exercise. MR relaxation parameters (T1, T2 and T2*) are characteristic of tissue composition and metabolic properties. With the recent advent of quantitative techniques that allow rapid acquisition of T1, T2 and T2* maps, we posited that an integrated treadmill exercise–quantitative relaxometry paradigm can rapidly characterize exercise‐induced changes in skeletal muscle relaxation parameters. Accordingly, we investigated the rest/recovery kinetics of T1, T2 and T2* in response to treadmill exercise in the anterior tibialis, soleus and gastrocnemius muscles of healthy volunteers, and the relationship of these parameters to age and gender. Thirty healthy volunteers (50.3 ± 16.6 years) performed the Bruce treadmill exercise protocol to maximal exhaustion. Relaxometric maps were sequentially acquired at baseline and for approximately 44 minutes post‐exercise. Our results show that T1, T2 and T2* are significantly and differentially increased immediately post‐exercise among the leg muscle groups, and these values recover to near baseline within 30–44 minutes. Our results demonstrate the potential to characterize the kinetics of relaxation parameters with quantitative mapping and upright exercise, providing normative values and some clarity on the impact of age and gender. Copyright © 2015 John Wiley & Sons, Ltd.